2015
DOI: 10.1038/cr.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis is associated with expansion of a motile, permissive and immunomodulatory CD16+ monocyte population via the IL-10/STAT3 axis

Abstract: The human CD14 + monocyte compartment is composed by two subsets based on CD16 expression. We previously reported that this compartment is perturbed in tuberculosis (TB) patients, as reflected by the expansion of CD16 + monocytes along with disease severity. Whether this unbalance is beneficial or detrimental to host defense remains to be elucidated. Here in the context of active TB, we demonstrate that human monocytes are predisposed to differentiate towards an anti-inflammatory (M2-like) macrophage activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(188 citation statements)
references
References 75 publications
13
163
0
4
Order By: Relevance
“…NF-κB plays a critical role in IL-6 transcription in addition to AP-1, NF-IL-6 and STAT3. STAT3 was shown to be a key signaling molecule in Mtb infected macrophages2829 and macrophages with activated STAT3 in the peripheral blood of TB patients were shown to be pathogenic associated with TB progression57. Consistent with this, our Western blot results show that ESAT-6 induced STAT3 phosphorylation in macrophages (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…NF-κB plays a critical role in IL-6 transcription in addition to AP-1, NF-IL-6 and STAT3. STAT3 was shown to be a key signaling molecule in Mtb infected macrophages2829 and macrophages with activated STAT3 in the peripheral blood of TB patients were shown to be pathogenic associated with TB progression57. Consistent with this, our Western blot results show that ESAT-6 induced STAT3 phosphorylation in macrophages (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Tuberculosis is associated with an expansion of immunomodulatory CD16 + monocyte population (39). Monocytes have been implicated in the establishment of Th17 response in autoimmune diseases (40, 41) and infection (42).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that circulating CD16+ monocytes isolated from TB patients had elevated cell surface expression of CD11b, TLR2, TLR5, CCR1, CCR2, and CCR5, and their ability to differentiate into DCs and induce T‐cell activation was compromised . Macrophages differentiated from these CD16+ monocytes were further shown to be skewed toward M2‐like activation status with elevated expression of CD163, MerTK, and STAT3 . The study concluded that during an active TB infection, human monocytes are predisposed to differentiate toward an anti‐inflammatory (M2‐like) macrophage activation program, exhibiting enhanced protease‐dependent motility, pathogen survival, and immuno‐modulatory properties.…”
Section: Macrophage Heterogeneity and M Tuberculosis Infectionmentioning
confidence: 97%